PENGARUH LKS IPA TERPADU MENGINTEGRASIKAN NILAI KARAKTER BERBASIS TIK PADA MATERI SBSPZA TERHADAP KOMPETENSI SISWA KELAS VIII SMPN 1 PADANG - Jully Ermisa; Asrizal Asrizal; Zulhendri Kamus (PILLAR OF PHYSICS EDUCATION, 2015)
Sciences learning material should be conducted in integrated form, but reality show that learning is still separated in the junior high school. The learning material which is used in printed form in the school. On the other hand, learning material doesn’t integrate characther values yet. Solution to solve this problem is to implement integrated sciences student worksheet by integrating character values based on ICT. Learning material on student worksheet consist of characteristic of materials, digestive system, additive and addictive substance. The purpose of this research is to investigate effect of integrated sciences student worksheet by integrating character values based on ICT toward students competence grade VIII in SMPN 1 Padang. The type of this research is a quasi experimental by randomized control group only design. The population of this research are students grade VIII in SMPN 1 Padang in academic year 2014/2015. As samples in this research are students grade VIII.F as experiment group and grade VIII.G as control group. Instrument to collect data consist of written test sheet of student learning outcome, observation sheet of student attitude, and performance sheet of student skill. Data analyses use compare mean test. Based on analyses of data can be stated, there are two research results. First, students competence in learning by using integrated sciences student worksheet by integrating the character values based on ICT on knowledge, attitude, and skill domain respectly 82.50, 82.87, and 83.45. Second, the use integrated sciences student worksheet by integrating the character values based on ICT on characteristic of materials, digestive system, additive and addictive substance gives significant effect toward students competence grade VIII in SMPN 1 Padang at significant level 95%